(3TQM cJGH SjHhjIs - (3Ydj Hf YjSi Hf Ydj Hf YHO Gddg CHi GdMSf GdQeGfis; (3YeQh Hf YKeGf Hf bfHQ GdMGQKj HGdhdGA, CHh HTQ, GdedbH SjHhjg,J (B180 (3g` s
(3ChdgG (B:s
(3heG GdTGgO ai bhdg ZjdGf OY PG hYLd NGhG jMbfG HOd HGdTMe EfG bO eddfG s
(3BNQgG (B:s
(3hCeG bhd HYV YdeGA HfhG Jeje agh Cbhi ai GdMPa dEf EdJbGA GdeKdKjf CTO EbJVGA ddJZjjQ ef EdJbGA GdeJbGQHjf hGdMeO ddg hMOg Je TQM SjHhjg s
(3dgG fSNI efgG CNQi JMJ Qbe (B88 (3fMhs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs